Rediscovery of Henckelia lachenensis (Gesneriaceae) in the Sikkim Himalaya after 176 Years - Lepcha , D.; Lepcha , P.T.; Ganesan , R.; Tangjang, S. (Rheedea, 2026)
Henckelia lachenensis (C.B.Clarke) D.J.Middleton & Mich.Möller, a species last collected in 1849 by J.D. Hooker from Lachen, Sikkim, has been rediscovered after 176 years during recent botanical explorations in Namchi district, Sikkim, Himalaya, India. This rediscovery confirms the species continued presence in its native habitat and provides updated locality, morphological details, and photographic documentation.